2023
DOI: 10.1002/aic.18113
|View full text |Cite
|
Sign up to set email alerts
|

Indirect urea electrooxidation by nickel(III) in alkaline medium: From kinetic and mechanism to reactor modeling

Abstract: This study consists in the determination of two kinetic laws of urea oxidation (UO) and electrooxidation (UEO) in alkaline media on nickel(III). Two kinds of active sites were examined, the first one derived from a Ni(OH)2 powder and the second from a massive nickel electrode. Partial orders of nickel(III) (two for UO and five UEO) enable to conclude about (i) the urea adsorption on two nickel(III) sites and (ii) that a multistep oxidation of urea occurs involving five nickel(III) site electroregenerations. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
0
9
1
Order By: Relevance
“…Note that contrary to Hopsort et al, , no NH 4 + formation was observed in this work. To clarify whether NH 4 + could be eventually formed and then oxidized electrochemically on Ni, cyclic voltammograms were acquired in the presence of ammonia for the Ni and Ni x Fe 1– x hydroxide electrodes (Figure S18).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Note that contrary to Hopsort et al, , no NH 4 + formation was observed in this work. To clarify whether NH 4 + could be eventually formed and then oxidized electrochemically on Ni, cyclic voltammograms were acquired in the presence of ammonia for the Ni and Ni x Fe 1– x hydroxide electrodes (Figure S18).…”
Section: Resultscontrasting
confidence: 99%
“…As to the products, early studies reported formation of N 2 , CO 2 , and H 2 O as the only products of the UOR on Ni. Meanwhile, recent works revealed that depending on the experimental conditions, other species, such as cyanate (NCO – ), ammonium (NH 4 + ), nitrite (NO 2 – ), nitrate (NO 3 – ), and nitrous oxide (N 2 O) can also be formed. A question thus arises as to whether the UOR products are influenced by the Fe incorporation in Ni­(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…− 1 for OCN − and NH 4 + (the formation of these species indirectly implies Ni(II)→Ni(III) oxidation system, as described in a previous work 16 ), − 6 for N 2 and − 6 for NO .…”
Section: Experimental Informationmentioning
confidence: 64%
“…Unfortunately, in the case of electrolysis with large urea conversion rates, complete mass balances (MB) are still scarcely established, even if complex mechanisms are always suggested. 12,13,15,16 Identifying all the byproducts requires the coupling of several analytical techniques, which is generally not done. Li et al 12 have revealed that the commonly used nickel-based catalysts exhibit a tendency to overoxidize urea into NO 2 − with about 80% of Faraday efficiency (FE).…”
Section: List Of Symbolsmentioning
confidence: 99%
See 1 more Smart Citation